Mafia infiltrations in times of crisis: Evidence from the Covid-19 shock - Marco Castelluccio; Lucia Rizzica (Institute for Fiscal Studies (IFS), 2023)
We analyse the risk of mafia capture of firms operating in the legal economy. Specifically, we study the relationship between firm performance and mafia infiltration. To overcome possible endogeneity concerns we exploit the abrupt drop in revenues caused by the (unexpected) Covid-19 related closures imposed in Spring 2020 in Italy. Our estimates reveal that the induced sudden and significant worsening of affected firms financial conditions increased the likelihood of them being infiltrated by mafia-connected entrepreneurs. According to our preferred specification, a 10% drop in revenues leads to a 4.8% increase in the probability of a firm being infiltrated by the mafia compared to the baseline. These effects, however, were partly offset by the extraordinary measures put in place by the government to support financially distressed firms. Heterogeneity in the effectiveness of the different measures provides indirect evidence that firms are more likely to resort to mafia lending when they face temporary difficulties in repaying their debts.
Keywords: D22; G32; K42; 330; organised crime; firm performance; Covid-19